Molecular Life Sciences An Encyclopedic Reference (Springer New York, 2018)
Molecular Life Sciences: An Encyclopedic Reference will focus on understanding biological phenomena at the level of molecules and their interactions that govern life processes. The work will include articles on genes and genomes, protein structure and function, systems biology using genomics and proteomics as the focus, molecular aspects of cell structure and function, unifying concepts and theories from biology, chemistry, mathematics and physics that are essential for understanding the molecular life sciences (including teaching perspectives and assessment tools), and basic aspects of the various experimental approaches that are used in the Molecular Life Sciences.